Root Cause Analysis of The Low Gas Volume Realization in Indonesia's Domestic Gas Market: a Case Study af PT EBL - Afrizon Setiawan; Arief Bimantoro Suharko (Sean Institute, 2024)
Natural gas is a low-carbon energy source, but Indonesia's gas absorption and domestic demand growth far lower than expected. For this reason, it is necessary to identify some of the main causes of problems in achieving gas absorption, especially for domestic pipeline gases. The causes of problems, categories, relation, and the search for alternative solutions to achieve targeted gas intake realization in the Indonesian domestic gas market are being considered. This study built on descriptive – analytical using qualitative approach. The data collected through questionnaires, interviews, and literature review. After identifying the cause of the problem, the next step is to use the fish-bone diagram approach to grouping the root causes, later on the Relative Importance Index (RII) is generated to rank the problem, then interrelationship diagram is created to look for the superiority of the relationship. Study and analysis results from questionnaires and in-depth interviews show that the root of the problem lies in the areas of reserves, project financing, product diversification, pricing and permit or administration. After grouping, strategic (reserves) and commercial groups are known to dominate over other risk groups.